Anesthetic considerations in children with asthma. Issue 2 (13th December 2021) - Regli, Adrian; Sommerfield, Aine; von Ungern‐Sternberg, Britta S.
Summary: Due to the high prevalence of asthma and general airway reactivity, anesthesiologists frequently encounter children with asthma or asthma‐like symptoms. This review focuses on the epidemiology, the underlying pathophysiology, and perioperative management of children with airway reactivity, including controlled and uncontrolled asthma. It spans from preoperative optimization to optimized intraoperative management, airway management, and ventilation strategies. There are three leading causes for bronchospasm (1) mechanical (eg, airway manipulation), (2) non‐immunological anaphylaxis (anaphylactoid reaction), and (3) immunological anaphylaxis. Children with increased airway reactivity may benefit from a premedication with beta‐2 agonists, non‐invasive airway management, and deep removal of airway devices. While desflurane should be avoided in pediatric anesthesia due to an increased risk of bronchospasm, other volatile agents are potent bronchodilators. Propofol is superior in blunting airway reflexes and, therefore, well suited for anesthesia induction in children with increased airway reactivity.